Optimization of Mulch Mat Production from Oil Palm Empty Fruit Bunches and its Effects on Growth Performance of Acacia Hybrid Seedlings on Sandy Tailings - Ibrahim, Wan Asma (2006)
For forest plantation establishment on sandy soils such as tin tailings in Malaysia; mulching is important during transplanting of plants for moisture retention, protection of soil surface from erosion due to heavy rain and strong wind, regulating the soil surface temperature, reducing leaching of nutrients from fertilizers and weed control. EFB has been recycled as a mulch and source of nutrients in the oil palm fields and also has the potential for mulching forest species on sandy soils. However, the EFB in its natural form is heavy, thorny and bulky and cannot be stored. Therefore, the EFB need to be transformed into a form that is convenient and economical for mulching. Although the EFB is already commercially processed into a more convenient light form, it is too thin and has lost most of the EFB original beneficial characteristics. Thus, an improved thicker mats should be developed. Earlier studies had shown that it was possible to produce mulch mat from EFB fiber using binders that allow the mat to decompose. However, the optimum processing parameters to obtain the mats of targeted thickness were not determined and knowledge on its decomposition and effect on plant growth is greatly lacking. Therefore, the objectives of this study were to, (i) determine optimum parameters for making EFB mat which is thicker, capable of absorbing and retaining water and decomposes slowly, (ii) investigate its decomposition and (iii) determine its effect on the growth performance of Acacia hybrid planted on sandy tin tailings.